Value of ultrasound in predicting the outcome of conservative treatment of testicular appendage torsion in children - Dongling Wu; Chanjuan Wang; Xiuzhen Yang; Jingjing Ye; Jianhua Mao (The Turkish Journal of Pediatrics)
Background: The treatment modalities for testicular appendage torsion in children are classified as conservative or surgical, and the choice is controversial.